Evaluation of genetic diversity and morphological variability in Stellaria media (L.) Vill. using RAPD marker (Bangladesh Journal of Plant Taxonomy, 2020)
Stellaria media (L.) Vill., known under the name of chickweed, is an annual medicinal plant in the family Caryophyllaceae. This species is distributed in the north regions of Iran. In the present study, the Random Amplified Polymorphic DNA (RAPD) technique was used to estimate infraspecific variation in different populations of Stellaria media. Samples from 11 populations were collected from different regions of the country during spring 2018. For RAPD investigations, populations were divided into three geographical regions. This study provides important data on the genetic diversity, population structure and morphological characteristics of Stellaria media. The AMOVA and Gst analyses showed that the populations of this species are genetically differentiated. Nm analysis revealed very low value of genetic diversity among the studied population and mantel test indicated isolation by distance occurred among them. The studied populations of S. media are differentiated in morphological characteristics and genetic content.Bangladesh J. Plant Taxon. 27(1): 173-184, 2020 (June)